Proximity effect at the interface He II-He I in microgravity environment - Kiknadze, L.; Mamaladze, Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The proximity effect causes the existence of some transition area with the gradual variation of the density of superfluid component instead of the sharp boundary at the level where the hydrostatic pressure realizes the phase transition He II-He I. In the microgravity environment the characteristic length of this effect increases, and more convenient conditions arise for measurements in the transition area. The problem of the expansion of thermodynamical potential in power series in the vicinity of He II-He I interface is considered. The critical values of the size of the superfluid area are determined.